(untitled) (Alternautas, 2022)
Covid-19 has exposed acute water inequalities within and between countries. Handwashing is widely seen as one of the most effective measures for preventing the spread of the virus. Yet more than two billion people lack sufficient access to clean water to carry out this basic task. Hundreds of millions of small-scale farmers also lack reliable access to irrigation water, making them extremely vulnerable to seasonal and climatic changes in water supply. The crisis triggered by the Covid-19 pandemic has exacerbated water inequalities as economic activity has collapsed, government revenues have plunged, and poverty has soared.